How does climate change affect optimal allocation of variable renewable energy? - Jakob Peter (Institute of Energy Economics at the University of Cologne (EWI), 2019)
Ongoing climate change affects complex and long-lived infrastructures like electricity systems. Particularly for decarbonized electricity systems based on variable renewable energies, there is a variety of impact mechanisms working differently in size and direction. Main impacts for Europe include changes in wind and solar resources, hydro power, cooling water availability for thermoelectric generation and electricity demand. Hence, it is not only important to understand the total effects, i.e., how much welfare may be gained when accounting for climate change impacts in all dimensions, but also to disentangle various effects in terms of their marginal contribution to the potential welfare loss. This paper applies a two-stage modeling framework to assess RCP8.5 climate change impacts on the European electricity system. Thereby, the performance of two electricity system design strategies - one based on no anticipation of climate change and one anticipating impacts of climate change - is studied under a variety of climate change impacts. Impacts on wind and solar resources are found to cause the largest system effects in 2100. Combined climate change impacts increase system costs of a system designed without climate change anticipation due to increased fuel and carbon permit costs. Applying a system design strategy with climate change anticipation increases the cost-optimal share of variable renewable energy based on additional wind offshore capacity in 2100, at a reduction in nuclear, wind onshore and solar PV capacity. Compared to a no anticipation strategy, total system costs are reduced.
Keywords: C61; Q41; Q42; Q48; Q54; 330; Climate Change; Variable renewable energy; Power system modeling